(untitled) (Ius Novum, 2024)
The article is of a scientific and research nature, and its subject matter covers the object of the crime of a creditor’s bribery (Article 302 § 2 of the Criminal Code). The article aims to resolve the doubts it raises. The author presents its development in Polish criminal law and analyses the features specified in the provision: a creditor, financial benefits, means of granting them, a promise to grant such benefits, acting to the detriment of other creditors, a relationship between a creditor’s action and an insolvency proceeding or a proceeding aimed at preventing bankruptcy, an insolvency proceeding, and other proceedings aimed at preventing bankruptcy. The interpretation of all these notions is proposed in the article based on doctrine and case law.